Tata Kelola Pemerintah Desa Dalam Penanganan Sampah Di Desa Subah Kecamatan Subah Kabupaten Batang - Maruf, Muhammad Annas; Maulani, Wihda (Universitas Muara Bungo, 2025)
This study aims to analyze the village government's governance in waste management in Subah Village, Subah Sub-district, Batang Regency. The issue addressed in this research is the accumulation of waste at the final disposal site (TPA) in Dukuh Tarub, located on Jalan Gunung Sari. This accumulation causes road narrowing, traffic congestion, and pollution. The objective of the research is to understand the governance of the Subah Village Government in handling waste issues. The method used is qualitative, with data collection techniques including observation, interviews, and documentation. The research was conducted at the Subah Village Government Office, Subah Sub-district, Batang Regency. This study utilizes the theory of good village governance according to Rustam (2021), with research indicators including: 1. Responsiveness, 2. Participation, 3. Transparency, and 4. Accountability. The results show that waste management in Subah Village is delegated to the community, while the Village Government only provides facilities and supporting infrastructure for waste management. Based on these indicators, it can be concluded that the Village Government has responded to community complaints by providing solutions to existing problems. However, community participation is limited to providing suggestions to the Village Government, while waste management is entirely handed over to the community, with the Village Government only facilitating the location and construction of waste collection points in the village